PENGARUH EFEKTIVITAS PEMBELAJARAN DI SEKOLAH DAN NIAT MASUK PERGURUAN TINGGI TERHADAP MINAT SISWA MENGIKUTI BIMBINGAN BELAJAR DI SMA NEGERI 3 SURAKARTA - -, Mohamad Iqbal Nur Syamsi -; -, Sunarto -; -, Jonet Ariyanto Nugroho - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The objectives of the study are to know; 1) the influence of the effectiveness of learning process at school and the intention of entering public university to the students? willingness of joining tuition classes of students of SMA Negeri 3 Surakarta, 2) the influence of the effectiveness of learning process at school to the students? willingness of joining tuition classes of the students of SMA Negeri 3 Surakarta, 3) the influence of intention of entering public university to the students? willingness of joining tuition classes of the students of SMA negeri 3 Surakarta. This Study was conducted at SMA Negeri 3 Surakarta and by quantitative research. the population of the study were 289 students and the sample were 75 students. The data collection technique was questionnaire. The data analysis technique was linear regression analysis, F-test and T-test also coefficient of determination. Based on the statistic test, it can be concluded as follows: (1) the result shows the positive and significant relation of the effectiveness of learning process at school and the intention of entering university simultaneously to the students? willingness of joining tuition classes of the students of SMA Negeri 3 Surakarta, the result was gotten by the help of SPSS, as known the Fstatistic = 15.205 > Ftable = 3.12 by using the significance number of 0.000<0.005, so it can be concluded simultaneously as the independent variable (the effectiveness of learning process at school and the intention of entering university) influenced the students? willingness of joining tuition classes of the students of SMA Negeri 3 Surakarta. (2) the test shows tcount = 3.090 > ttable = 1.993, so Ho was accepted and Ha was denied. It means that partially, the effectiveness of learning process at school doesn?t gave positif and significant influence to the students? willingness of joining intuition classes of the students of SMA Negeri 3 Surakarta. (3) the test shows tcount = 3.243 > ttable = 1.993, so Ha was denied and Ha was Accepted. It means that partially, the intention of entering public university influenced positively and significantly to the willingness of joining tuition classes of the students of SMA Negeri 3 Surakarta.